Better than Ploughing - Buchanan, James M. (PSL Quarterly Review, 2013)
Contribution to a series of recollections and reflections on professional experiences of distinguished economists. Article originally published in vol. 39 n. 159 (1986) of Banca Nazionale del Lavoro Quarterly Review. The author, who shortly after writing this autobiographical note went on to win the Nobel Memorial Prize in Economic Sciences in 1986, draws for the title of the article from Frank Knight, to whom he declares intellectual indebtedness. He describes his academic career from the personal origins in the poor agricultural region of Tennessse, to the creation of the Thomas Jefferson Center for Studies in Political Economy. JEL Codes: B31, D71, D72